1992
DOI: 10.1128/jvi.66.12.7128-7135.1992
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutation in the human immunodeficiency virus type 1 reverse transcriptase gene that encodes cross-resistance to 2',3'-dideoxyinosine and 2',3'-dideoxycytidine

Abstract: We have used the technique of in vitro selection to generate variants of human immunodeficiency virus type 1 (H1V-i) that are resistant to 2',3'-dideoxyinosine (ddl) and cross-resistant to 2',3'-dideoxycytidine (ddC). The complete reverse transcriptase (RT)-coding regions, plus portions of flanking sequences, of viruses possessing a ddI-resistant phenotype were cloned and sequenced by polymerase chain reaction (PCR)-based methods. We observed that several of these viruses possessed mutations at amino acid site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(100 citation statements)
references
References 37 publications
(35 reference statements)
7
92
0
1
Order By: Relevance
“…The M184V mutation is a well studied and important HIV-1 drug-resistance mutation [15]. Many resistance algorithms still consider the M184V mutation to confer some degree of resistance to ddI [13], but several studies have now reported that a single M184V mutation may not affect the clinical response to ddI [11]. However, most in vivo data have been collected from studies of the major viral population using direct sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M184V mutation is a well studied and important HIV-1 drug-resistance mutation [15]. Many resistance algorithms still consider the M184V mutation to confer some degree of resistance to ddI [13], but several studies have now reported that a single M184V mutation may not affect the clinical response to ddI [11]. However, most in vivo data have been collected from studies of the major viral population using direct sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…The M184V mutation can also be selected in vitro by abacavir (ABC) [8] and didanosine (ddI) [9]. However, it has been reported that a single M184V mutation may not affect the clinical response to ABC [10] and ddI [11]. Hence, the resistance effect of the M184V mutation may be present only in the presence of additional mutations in the RT gene [12].…”
Section: Introductionmentioning
confidence: 99%
“…ddC or ddI treatment (7,8,10,28), and the 184V mutation is associated with high-level resistance to 3TC and (Ϫ)-2Ј-deoxy-3Ј-thiacytidine (FTC) (1,25,28). The 65R mutation has also previously been reported to give low-level resistance to 3TC (11), as confirmed in this study, and to 9-(2-phosphonylmethoxyethyl)adenine (12). The fourth mutation, Y115 to F, has not been observed previously in resistance selection studies, although this residue has been shown by site-directed mutagenesis to be critical for enzyme activity (2,3,20).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then washed extensively and maintained in tissue culture medium in either the absence or the presence of subinhibitory concentrations of 3TC, beginning with 0.01 M. The medium was changed twice weekly; each replacement contained an increased drug concentration, as follows: 0.01, 0.05, 0.2, 1, 2.5, 10, 25, 100, 250, 500, and 750 M. Culture fluids (0.5 ml) from each passage were used to infect fresh C8166 cells as described previously (7). Cultures were monitored for the presence of RT activity and the presence of a cytopathic effect as described previously (9). After 8 and 24 weeks (final 3TC concentration, 2.5 or 750 M), viral variants of pJ5 and pC8 contained either the M184I or M184V substitutions, respectively, and were capable of growth in the presence of greater than 500 and 2,000 M 3TC, i.e., more than 1,000-and 4,000-fold the usual inhibitory drug concentration, respectively ( Table 1).…”
mentioning
confidence: 99%